2010
DOI: 10.1007/s00424-009-0769-5
|View full text |Cite
|
Sign up to set email alerts
|

ClC transporters: discoveries and challenges in defining the mechanisms underlying function and regulation of ClC-5

Abstract: The involvement of several members of the chloride channel (ClC) family of membrane proteins in human disease highlights the need to define the mechanisms underlying their function and the consequences of disease-causing mutations. Despite the utility of high-resolution structural models, our understanding of the molecular basis for function of the chloride channels and transporters in the family remains incomplete. In this review, we focus on recent discoveries regarding molecular mechanisms underlying the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 134 publications
(248 reference statements)
0
19
0
Order By: Relevance
“…Nevertheless, the universality of this mechanism has been hard to reconcile with all of the published data. Both the ClC-3 and ClC-4 knock-out mice do not have gross endosomal acidification defects [15] while the requirement of ClC-7 as an electric shunt during lysosomal acidification has been disputed [6,18,19], suggesting that the role of Cl À /H þ exchange in endo-lysosome acidification is more complicated than originally proposed. Whether these discrepancies reflect the compensatory and/or overlapping activities of family members, experimental, or tissue-type differences will require further study.…”
Section: This Would Imply That Intracellular Clcs Function To Transpomentioning
confidence: 98%
See 2 more Smart Citations
“…Nevertheless, the universality of this mechanism has been hard to reconcile with all of the published data. Both the ClC-3 and ClC-4 knock-out mice do not have gross endosomal acidification defects [15] while the requirement of ClC-7 as an electric shunt during lysosomal acidification has been disputed [6,18,19], suggesting that the role of Cl À /H þ exchange in endo-lysosome acidification is more complicated than originally proposed. Whether these discrepancies reflect the compensatory and/or overlapping activities of family members, experimental, or tissue-type differences will require further study.…”
Section: This Would Imply That Intracellular Clcs Function To Transpomentioning
confidence: 98%
“…Promptly, the remainder of the family was identified, but it was not until much later that the intracellular family members (ClC-3-7) were found to actually function as Cl À /H þ antiporters, due in part to the inherent difficulties of working with intracellular ion transporters [15]. Furthermore, these studies identified a single glutamate residue in the pore region which mediates the interchange from antiport exchanger to pure anion channel [13,14].…”
Section: Ion Homeostasis and Endosome Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ClC family comprises both Cl − channels and Cl − /H + antiporters [94,215]. ClC5 is a Cl − /H + antiporter that is expressed primarily in endosomal membranes in the proximal tubules and is responsible for endosomal acidification, a role it carries out in collaboration with V-ATPase.…”
Section: CLmentioning
confidence: 99%
“…About half of all CLCs are secondary active transporters, catalyzing the stoichiometric exchange of two Cl Ϫ ions for one proton, while the other half are passive channels, catalyzing rapid downhill movement of Cl Ϫ (1, 109, 120). Both types play important roles in kidney tubular function (23,26,30,86,88,110,151). In the channel branch of the family, the two kidney-specific homologs, ClC-Ka and ClCKb, have central roles in tubular Cl Ϫ reabsorption that make them important targets for novel therapeutic interventions (36,41,61,63,65,75).…”
Section: Clc-ka/bmentioning
confidence: 99%